2016
DOI: 10.1186/s12877-016-0369-0
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional construct of life satisfaction in older adults in Korea: a six-year follow-up study

Abstract: BackgroundAging raises wide-ranging issues within social, economic, welfare, and health care systems. Life satisfaction (LS) is regarded as an indicator of quality of life which, in turn, is associated with mortality and morbidity in older adults. The objective of this study was to identify the relevant predictors of life satisfaction and to investigate changes in a multidimensional construct of LS over time.MethodsThis analysis utilized data from the large-scale, nationally representative Korean Retirement an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 69 publications
1
37
0
4
Order By: Relevance
“…Adults’ independence from their parents in comparison with adolescents’ independence might explain the insignificant effect. Furthermore, the trend in SRH and family LS of Taiwanese older adults corroborates the results found in Western countries …”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Adults’ independence from their parents in comparison with adolescents’ independence might explain the insignificant effect. Furthermore, the trend in SRH and family LS of Taiwanese older adults corroborates the results found in Western countries …”
Section: Discussionsupporting
confidence: 86%
“…Earlier research showed that getting along with adult children increased LS among Taiwanese older women, but this did not apply to the family LS of older adults. As shown in previous research, LS is a multidimensional construct . Financial strain is more related to family LS than to other dimensions of LS .…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations